La lutte contre le sida au Maroc : opportunités et limites pour l’accès aux soins des personnes en migration - Camille Fidelin (L’Année du Maghreb)
Health questions the place of people in migration in a host society. Most of the time perceived as a public health issue, it is above all a question of respect for human rights and the choice of host society. In Morocco, the response to HIV has been used as an advocacy opportunity by associations to develop access to primary care for people in migration, in the context of the new migration policy initiated in 2014. A participant observation within the “migrant protection” programme of the Association de lutte contre le Sida (ALCS) in Rabat and a survey of the association’s volunteers carried out in 2014 highlighted the importance of the community health lever in opening up care opportunities for people migrating to Morocco: the association’s volunteers becoming focal points. Nevertheless, this strategy is hampered by various factors: the difficulty of extending the system linked to a specific disease to all types of care, the lack of basic medical cover for all migrants present on the Moroccan territory, and geographically limited access to the cities in which the associations are present. The political context, marked by a recurrence of repressive episodes towards migrant populations in Morocco, tends to criminalise the latter and also prevents the implementation of a sustainable policy of access to health care.